The Progression in the Agriculture Area By means of IoT (International Journal of Innovative Research in Computer Science & Technology, 2021)
The agricultural industry plays an  essential role in overcoming the food scarcity scenarios  for food security globally in the rising population  scenario. In the agricultural sector, mechanization has  improved various crop production, creating a new era for  attaining agricultural precision. With the development of  agricultural equipment, conventional usage of farm  machinery has lately been changed. The realm of  precision agriculture has transformed this breakthrough.  The numerous types of high-quality efficient sensors have  been used in the field of productive irrigation, fungicides,  fertilizers and disease control in diverse plant. This  approach has increased agricultural yield therefore  reducing production costs. In agriculture, the introduction  of Internet of Things (IoT) technology has enabled  farmers to relieve themselves by utilizing Smartphone  applications and high-speed internet. By comparing the  data received from a farm with previously recorded  standard charts in the database, these systems offer all the  information required for a farmer to manage a crop  accurately. In order to guarantee precision in agriculture,  this innovation in the automation of agricultural  equipment also enables farmers to increase production,  solving the world's food crisis. This article examines the  progress in the agricultural sector by integrating IoT  technology for the precision farming.
Keywords: Agriculture; Equipment; Farming; Irrigation; Machinery